La llegada de Maximiliano a la tierra de los pueblos bárbaros - Jancsó, Katalin (Acta Hispanica, 2008)
The author examines a specific aspect of the brief period of Maximilian's reign as the Emperor of Mexico. The spring of 1864 opened an interesting and controversial era of Mexican history. After arriving at Mexico and being proclaimed Emperor with the help of the Mexican Conservatives, Maximilian I., Archduke of Austria and Prince Royal of Hungary and Bohemia reigned in a surprisingly liberal spirit, with the principal aim of modernizing Mexico. The Mexican liberals, led by Benito Juárez, did all they could to get rid of the foreign emperor, and finally executed him the 19th of July, 1867. During his brief reign of three years, both Maximilian and his wife, the empress Charlotte of Belgium manifested profound interest in the situation of the native Indians who made up the vast majority of Mexico's population and had great expectations towards the emperor. A dedicated liberal, Maximilian considered all Mexican citizens should be granted the same rights, and adopted various measures to improve the condition of the natives, and help their integration in the Mexican nation through the process of mestizaje. The author presents the circumstances of Maximilian's arrival at Mexico, his reception, the measures introduced by the Emperor in the protection of the Indian population and the circumstances that led to the creation of the „Junta Protectora de las Clases Menesterosas”, organization representing the interests of the poor, as described in the press of the era.